Changes of serum amino acid profiles by an epidermal growth factor receptor mutation and benzo[a]pyrene in mouse lung tumorigenesis. Issue 4 (31st May 2016) - Lin, Pinpin; Chen, Yi-Rong; Chen, Chao-Yu; Chang, Ya-Ting; Chen, Jhih-Sheng; Tsai, Ming-Hsien; Kuo, Cheng-Chin; Lee, Hui-Ling
Graphical Abstract: Abstract: Studies suggest that gene mutation and carcinogen exposure contribute to lung tumorigenesis including a mutation of epidermal growth factor receptor (EGFR) and exposure to benzo[ a ]pyrene (BaP). However, the interaction between EGFR mutation and BaP exposure during lung tumorigenesis is unclear. Metabolomics has become an important tool in clinical research and has been utilized to help our understanding of mechanisms and to identify indicators of cancers. This study's aim was to identify the changes in metabolite profiles in mice associated with an EGFR exon 21 deletion and/or BaP treatment-induced lung tumorigenesis. While the EGFR mutation increased the incidence of lung adenoma in transgenic mice (EGFR mutant mice) at 32 weeks of age, exposure to BaP caused the onset of lung tumorigenesis in these mice as early as 16 weeks after exposure. Using a metabolomics strategy involving liquid chromatography-mass spectrometry in conjunction with principal component analysis and confirmation by liquid chromatography triple quadrupole tandem mass spectrometry, we demonstrated that the serum amino acid profiles of these mice were changed. A total of eight amino acid concentrations were lower in EGFR mutant mice than in wild-type mice at 32 weeks of age. Five amino acids were lower in tumor-bearing mice than in non-tumor-bearing EGFR mutant mice at 10th week post-treatment of BaP, namely phenylalanine, tyrosine, alanine, proline, and threonine. Our results suggest that gene mutation and carcinogen exposure-induced lung adenomas share some common mechanisms. Changes in serum amino acid profiles may be early indicators of lung tumorigenesis.